The Bacterial Flagellar Motor: Insights Into Torque Generation, Rotational Switching, and Mechanosensing - Guo, Shuaiqi; Liu, Jun (Frontiers in Microbiology, 2022)
The flagellar motor is a bidirectional rotary nanomachine used by many bacteria to sense and move through environments of varying complexity. The bidirectional rotation of the motor is governed by interactions between the inner membrane-associated stator units and the C-ring in the cytoplasm. In this review, we take a structural biology perspective to discuss the distinct conformations of the stator complex and the C-ring that regulate bacterial motility by switching rotational direction between the clockwise (CW) and counterclockwise (CCW) senses. We further contextualize recent in situ structural insights into the modulation of the stator units by accessory proteins, such as FliL, to generate full torque. The dynamic structural remodeling of the C-ring and stator complexes as well as their association with signaling and accessory molecules provide a mechanistic basis for how bacteria adjust motility to sense, move through, and survive in specific niches both outside and within host cells and tissues.